O Projeto de integraç\~ao do Rio S\~ao Francisco, obras complementares para o aumento da oferta hídrica e convivência com as secas - César Nunes de Castro; Monise Terra Cerezini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The S\~ao Francisco Integration Program (PISF), known as the S\~ao Francisco transposition, represents the largest water infrastructure project aimed at increasing water supply in the driest region of Brazil. The level of success achieved in this regard can be enhanced through complementary measures to the PISF. The arsenal of public policies implemented by the State to mitigate the effects of low regional water availability is broad and is not limited exclusively to water infrastructure works. From the analysis of public policies complementary to the Integration Project, it was found that both at the federal and state levels, the recommended water infrastructure has great potential to increase water security in the region benefited by the transposition. PISF and its various sections, as well as the complementary works located in the benefited states, which will integrate the full operation of the transposition, are fundamental to increase the supply of water, primarily for human and animal use, mitigating the effects of low regional water availability and droughts that afflict the region. For rural supply, it is important to think about other alternatives for water sources, since the PISF will not contribute significantly to serving this population, given the distance and cost involved in disseminating the water infrastructure to serve this dispersed rural population. The analysis of public policies related to the concept of coexistence with drought showed that the Água para Todos Program and the Cisterns Program represent an excellent cost-benefit alternative to increase water availability for human use by the rural population.
10419/284863
Keywords: Q18; Q25; 330; water supply; water security; S\~ao Francisco River Basin water transfer